Orientalist aesthetics : art, colonialism, and French North Africa, 1880-1930 - Benjamin, Roger (University of California Press, 2003)
Lavishly illustrated with exotic images ranging from Renoir's forgotten Algerian oeuvre to the abstract vision of Matisse's Morocco and beyond, this book is the first history of Orientalist art during the period of high modernism. Roger Benjamin, drawing on a decade of research in untapped archives, introduces many unfamiliar paintings, posters, miniatures, and panoramas and discovers an art movement closely bound to French colonial expansion